Crystal structure of human purine nucleoside phosphorylase complexed with acyclovir - dos Santos, D. M.; Canduri, F.; Pereira, J. H.; Dias, MVB; Silva, R. G.; Mendes, M. A.; Palma, Mario Sergio [UNESP]; Basso, L. A.; de Azevedo, W. F.; Santos, D. S. (Elsevier B.V., 2003)
In human, purine nucleoside phosphorylase (HsPNP) is responsible for degradation of deoxyguanosine and genetic deficiency of this enzyme leads to profound T-cell mediated immunosuppression. PNP is therefore a target for inhibitor development aiming at T-cell immune response modulation and has been submitted to extensive structure-based drug design. This work reports the first crystallographic Study of human PNP complexed with acyclovir (HsPNP:Acy). Acyclovir is a potent clinically useful inhibitor of replicant herpes simplex virus that also inhibits human PNP but with a relatively lower inhibitory activity (K-i=90muM). Analysis of the structural differences among the HsPNP:Acy complex, PNP apoenzyme, and HsPNP:Immucillin-H provides explanation for inhibitor binding, refines the purine-binding site, and can be used for future inhibitor design. (C) 2003 Published by Elsevier B.V.
Keywords: PNP; synchrotron radiation; Structure; acyclovir; drug design